Kashgar revisited Uyghur studies in memory of Ambassador Gunnar Jarring - Bellér-Hann, Ildikó; Schlyter, Birgit N.; Sugawara, Jun 1966- (Brill's inner Asian library, 2017)
Building on the rich scholarly legacy of Gunnar Jarring, the Swedish Turkologist and diplomat, the fourteen contributions by sixteen authors representing a variety of disciplines in the humanities and the social sciences provide an insight into ongoing research trends in Uyghur and Xinjiang Studies. In one way or other all the chapters explore how new research in the fields of history, linguistics, anthropology and folklore can contribute to our understanding of Xinjiang's past and present, simultaneously pointing to those social and knowledge practices that Uyghurs today can claim as part of their traditions in order to reproduce and perpetuate their cultural identity.